2020
DOI: 10.1002/iub.2415
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0109046 promotes the malignancy of endometrial carcinoma cells through the microRNA‐105/SOX9/Wnt/β‐catenin axis

Abstract: Emerging evidence suggests the important involvements of circular RNAs (cir-cRNAs) in cancer progression. This study focuses on the function of Circ_0109046 on the malignancy of endometrial carcinoma (EC) cells and the molecules involved. First, high expression of Circ_0109046 was found in EC tissues compared to the adjacent tissues, and it predicted unfavorable prognosis in patients. Similarly, high expression of Circ_0109046 was confirmed in EC cells relative to that in normal endometrial epithelial cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A vast array of abnormally expressed circRNAs, such as circ_0005276 [ 2 ], circ_0004390 [ 3 ], and circPIP5K1A [ 4 ], have been discovered in ovarian cancer, which are closely related to the clinicopathological features and prognosis of ovarian cancer patients; moreover, functional experiments further confirmed their involvement in the tumorigenesis of ovarian cancer, implying that circRNAs may be promising candidates for the development of ovarian cancer therapeutic method. Recently, research showed that circ_0109046 was highly expressed in endometrial cancer and predicted poor prognosis; functionally, circ_0109046 lack inhibited the proliferation and invasiveness of endometrial cancer cells by miR-105 [ 5 ]. However, the action and mechanism of circ_0109046 on the ovarian cancer cell malignant phenotypes remain vague.…”
Section: Introductionmentioning
confidence: 99%
“…A vast array of abnormally expressed circRNAs, such as circ_0005276 [ 2 ], circ_0004390 [ 3 ], and circPIP5K1A [ 4 ], have been discovered in ovarian cancer, which are closely related to the clinicopathological features and prognosis of ovarian cancer patients; moreover, functional experiments further confirmed their involvement in the tumorigenesis of ovarian cancer, implying that circRNAs may be promising candidates for the development of ovarian cancer therapeutic method. Recently, research showed that circ_0109046 was highly expressed in endometrial cancer and predicted poor prognosis; functionally, circ_0109046 lack inhibited the proliferation and invasiveness of endometrial cancer cells by miR-105 [ 5 ]. However, the action and mechanism of circ_0109046 on the ovarian cancer cell malignant phenotypes remain vague.…”
Section: Introductionmentioning
confidence: 99%
“…25 Circ_0109046 absence hindered cell growth and epithelial-mesenchymal transition in EC. 26 In another example, Li and his colleague 27 indicated circ_0109046 depletion impeded cell aggressiveness and promoted cell apoptosis in EC in vitro. CircZNF124, a circRNA, has been reported to inhibit lung cancer processes by miR-498/YES proto-oncogene 1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of ovarian cancer, HK2, which is regulated by the tumor microenvironment, controls the production of lactic acid and regulates the expression of MMP9/NAONG/SOX9 through the FAK/ERK1/2 signaling pathway, which leads to ovarian cancer metastasis and stem regulation [ [70]. SOX9 expression also showed a signi cant gradual increase from normal to grade 1 to grade 2/3 tumors [71].…”
Section: Discussionmentioning
confidence: 99%